Decreased stress-induced depression-like behavior in lactating rats is associated with changes in the hypothalamic-pituitary-adrenal axis, brain monoamines, and brain amino acid metabolism. (4th July 2019) - Hamada, Mizuki; Nishigawa, Takuma; Maesono, Saori; Aso, Kenta; Ikeda, Hiromi; Furuse, Mitsuhiro
Abstract: Depression-like behavior during lactation may relate to changes in the hypothalamic-pituitary-adrenal (HPA) axis, brain monoamines, and brain amino acid metabolism. This study investigated how the behavior, HPA axis activity, brain monoamines, and brain free amino acid metabolism of rats were changed by stress or lactation period. Rats were separated into four groups: (1) control lactating ( n = 6), (2) stress lactating ( n = 6), (3) control virgin ( n = 7), and (4) stress virgin ( n = 7) and restrained for 30 min a total of ten times (once every other day) from postnatal day (PND) 1. Depression-like behavior in the forced swimming test (FST) on PND 10 and concentration of corticosterone in plasma, as well as monoamines and L-amino acids including β-alanine, γ-aminobutyric acid, cystathionine, 3-methyl-histidine and taurine in the prefrontal cortex and hypothalamus on PND 19 were measured. The plasma corticosterone concentration, measured just after restraint stress, was significantly higher in the stress groups, versus the control groups, but there were no significant differences between control and stress lactating groups. Depression-like behavior (immobility) in the FST was significantly lower in the lactating groups, versus the virgin groups. Stress enhanced dopamine and glutamate, and decreased threonine and glycine concentrations in the hypothalamus. In addition, 3-methoxy-4-hydroxyphenylglycol (MHPG), threonine and ornithine concentrations in the prefrontal cortex were significantly higher in the lactating groups compared with the virgin groups. Changes in plasma corticosterone concentration, monoamine, and amino acid metabolism may relate to stress-induced depression-like behavior in lactating rats. Lay summary: This study revealed that reduced depression-like behavior in lactating, relative to virgin rats, was associated with changes in monoamine and amino acid metabolism in the prefrontal cortex of the brain. In addition, the effect of stress on monoamine and amino acid metabolism is prominently observed in the hypothalamus and may be related to neuroendocrine stress axis activity and secretion of corticosterone. This study suggested that stress-induced depression-like behavior may be associated with several changes in the stress axis, brain monoamines, and brain amino acid metabolism. These parameters were associated with attenuated depression-like behavior in lactating rats.